2019
DOI: 10.1002/adma.201803444
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Carbon Nanomaterials for Electrochemical Sodium Storage and Capture

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/adma.201803444. Electrochemical sodium storage and capture are considered an attractive technology owing to the natural abundance, low cost, safety, and cleanness of sodium, and the higher efficiency of the electrochemical system compared to fossil-fuel-based counterparts. Considering that the sodium-ion chemistry often largely deviates from the lithium-based one despite the physical and chemical sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(54 citation statements)
references
References 195 publications
0
53
0
Order By: Relevance
“…Different forms of carbon-based materials, includingg raphite-based carbon,g raphene, and soft and hard carbons (HCs), have been investigated as anode materials in SIBs. [47] Theoretically,i th as been confirmed that Na ions can be easily intercalated into carbonaceousm aterials with an interlayer distance higher than 0.37 nm, [48] as shown in Figure 3 FIG003 a. As the interlayer distance between graphite sheets is only 0.335 nm, natural graphite only possesses al ow theoretical charge-storage capacity.S imilarly,N ai onsc annotp enetrate into voids of soft carbon due to itsi nterlayer distance (< 0.35 nm) and random orientation of layers,a nd as such Na ions tend to adsorb on the surfacea nd defects ites of soft carbon.…”
Section: Principle and Mechanismmentioning
confidence: 84%
“…Different forms of carbon-based materials, includingg raphite-based carbon,g raphene, and soft and hard carbons (HCs), have been investigated as anode materials in SIBs. [47] Theoretically,i th as been confirmed that Na ions can be easily intercalated into carbonaceousm aterials with an interlayer distance higher than 0.37 nm, [48] as shown in Figure 3 FIG003 a. As the interlayer distance between graphite sheets is only 0.335 nm, natural graphite only possesses al ow theoretical charge-storage capacity.S imilarly,N ai onsc annotp enetrate into voids of soft carbon due to itsi nterlayer distance (< 0.35 nm) and random orientation of layers,a nd as such Na ions tend to adsorb on the surfacea nd defects ites of soft carbon.…”
Section: Principle and Mechanismmentioning
confidence: 84%
“…Carbon-based materials, with their excellent electrical, chemical, and structural properties, have been widely used as electrodes in ESS, such as supercapacitors, lithium-ion batteries, etc. [103] The porous structure and continuous connectivity of the carbon effectively transfers electrons and ions in an ESS, and it also acts as a medium for other…”
Section: Electrochemical Energy Storagementioning
confidence: 99%
“…Considering the limited lithium supplies present in the earth crust (20 ppm), and the growing need for large‐scale renewable energy storage, there is a desire to develop alternative rechargeable battery chemistries based on more earth‐abundant elements, such as sodium (earth abundance 23 000 ppm), and potassium (earth abundance 17 000 ppm) . The past decade has witnessed the rapid development in sodium‐ion battery (SIB) research, whereas the potassium‐ion battery (PIB) remains much less explored . One of the main reasons for this reality is the lack of suitable high‐performance PIB anode .…”
Section: Introductionmentioning
confidence: 99%